2021
DOI: 10.1038/s41598-021-81310-8
|View full text |Cite
|
Sign up to set email alerts
|

No fitness cost associated with Asn-2041-Ile mutation in winter wild oat (Avena ludoviciana) seed germination under various environmental conditions

Abstract: Knowledge about the fitness cost imposed by herbicide resistance in weeds is instrumental in devising integrated management methods. The present study investigated the germination response of ACCase-resistant (R) and susceptible (S) winter wild oat under different environmental conditions. The DNA of the plants was sequenced after being extracted and purified. The segregated F2 seeds were subjected to various temperatures, water potentials, NaCl concentrations, different pHs, darkness conditions, and burial de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 44 publications
0
1
0
Order By: Relevance
“…Emergence of G. carolinianum seedlings was higher than 80% at zero and 1 cm depths, whereas no emergence was observed when the seeds were buried under 7 cm of soil (Liu et al, 2018). Similarly, emergence of A. sterilis seeds was the highest when buried at 0 to 2 cm, but declined thereafter and was nil at 15 cm (Hassanpour-bourkheili et al, 2021b). Since the highest emergence percentage was observed at 1 cm burial depth (Figures 5 and 6), the seeds were buried at this depth for the flooding experiment.…”
Section: Response Of Geranium Dissectum Seeds To Phmentioning
confidence: 87%
See 1 more Smart Citation
“…Emergence of G. carolinianum seedlings was higher than 80% at zero and 1 cm depths, whereas no emergence was observed when the seeds were buried under 7 cm of soil (Liu et al, 2018). Similarly, emergence of A. sterilis seeds was the highest when buried at 0 to 2 cm, but declined thereafter and was nil at 15 cm (Hassanpour-bourkheili et al, 2021b). Since the highest emergence percentage was observed at 1 cm burial depth (Figures 5 and 6), the seeds were buried at this depth for the flooding experiment.…”
Section: Response Of Geranium Dissectum Seeds To Phmentioning
confidence: 87%
“…This process is defined as the events that start with the uptake of water by the seed and end with radicle protrusion (Talská et al, 2020). Germination of non-dormant seeds is influenced by various environmental factors, including temperature, water potentials, salinity, light and darkness, pH and burial depth (Hassanpour-bourkheili et al, 2021b).…”
Section: Introductionmentioning
confidence: 99%
“…Hassanpour-Bourkheili et al (2020) found increased seed production of imazamox-susceptible than resistant biotypes of wild poinsettia (Euphorbia heterophylla L.), suggesting a fitness penalty for the resistant phenotype [38]. However, investigating the germination response of ACCase-resistant and ACCase-susceptible sterile oat under different environmental conditions, Hassanpour-Bourkheili et al (2021) reported no fitness cost for seed output [20]. Fitness costs associated with resistance to ACCase inhibitors have been reported to vary significantly among species, resistance mechanisms, the specific mutated allele conferring resistance, genetic backgrounds, experimental conditions (such as greenhouse or field settings), and competitive and non-competitive environments, as well as environmental conditions [39][40][41].…”
Section: Number Of Tillers and Of Seeds Per Plantmentioning
confidence: 99%
“…A better understanding of weed fitness under drought conditions could help in predicting the future population dynamics of herbicide-resistant weeds and their management [19]. Hassanpour-Bourkheili et al (2021) investigated the germination response of ACCase-resistant (R) and ACCase-susceptible (S) sterile oat under various environmental conditions such as different temperatures, water potentials, NaCl concentrations, different pHs, darkness conditions, and burial depths [20]. They found no differences in the germination response between the R and S sterile oat plants under the aforementioned conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The fitness cost of herbicide resistance may occur for the following reasons: (1) mutations in the gene encoding the herbicide target enzyme may disrupt the plant function and metabolism [81], (2) the resources required for growth and propagation may be rerouted to defense due to the evolution of resistance [85], and (3) resistant alleles may result in pleiotropic effects, which might adjust ecological relationships. For instance, the plant may become less attractive for pollinators due to higher concentrations of some secondary metabolites [86][87][88][89]. The fitness cost imposed by herbicide resistance may be quantified by measuring various characteristics of the species, including germination [83], phenology, vegetative characteristics, fecundity, and yield [90].…”
Section: Fitness Cost Of Herbicide Resistance In Phalaris Sppmentioning
confidence: 99%